Detección de virus nucleocitoplasmáticos de ADN de gran tamaño en sistemas lacustres naturales a diferentes pisos altitudinales de la provincia de Loja - Ortiz Gordillo, Joseph David (2024)
This research focuses on the presence of giant viruses in lacustrine systems of the province of Loja, with the aim of exploring the influence of different altitudinal gradients on their distribution. The study was conducted in four lagoons in the province of Loja (Pindal, Chayazapa, Oñacapac, Laguna Negra). Monoxenic cultures of Acanthamoeba castellanii ATCC 30010 were used, infected with water samples from different lacustrine systems to observe the cytopathic effects caused by the potential presence of large nucleocytoplasmic DNA viruses (NCDLVs). The research highlights the environmental variability of each area, considering factors such as pH, temperature, and dissolved oxygen, which may influence the presence of these viruses. The results show that cytopathic effects were observed only in the Oñacapac lagoon (effects such as: cell rounding after 48 hours of infection, morphological change, and amoebal elongation after 72 hours), which is characterized as a lentic and eutrophic water body, unlike other sampled lagoons that exhibited characteristics of lotic water bodies with low levels of eutrophication. This suggests that environmental stability and nutrient availability are key factors for the presence of giant viruses and their hosts, rather than altitude. The results demonstrate that specific environmental conditions, such as eutrophication and ecosystem stability, are more relevant than altitudinal gradients for the presence of giant viruses. Keywords: Nucleocytoplasmic DNA viruses, lacustrine systems, altitudinal gradients, Acanthamoeba castellanii, cytopathic effects